Design and Simulation of Phase-Locked Loop Controller Based Unified Power Quality Conditioner Using Nonlinear Loads - C. Prakash; N. Suparna (Institute of Advanced Engineering and Science, 2012)
This project presents a power quality improvement of unified power quality conditioner (UPQC) to compensate current and voltage quality problems of sensitive loads. The UPQC consists of the series and shunt converter having a common dc link. The series converter mitigates voltage sag from the supply side and shunt converter eliminates current harmonics from the nonlimear load side. The developed controllers for series and shunt converters are based on a reference signal generation method (phase-locked loop). The dc link control strategy is based on the fuzzy-logic controllers. The conventional method using dq transformation to show the superiority of the proposed sag detection method. A fast sag detection method is also is presented. The efficiency of the proposed system is tested through simulation studies using the MATLAB/SIMULINK environment.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.376